Impact of Large Scale Distributed New Energy Access on Provincial Power Grid Stability - Jiawei LI; Guanyu ZHANG (Zhongguo dianli)
Based on the transient characteristics of different types of distributed new energy, typical models are established and aggregated into active comprehensive load models, which can be used for safety and stability analysis of provincial power grids. The results show that the proposed method can effectively reflect the complex impact of the low voltage ride through and wave sealing characteristics of new energy on the stability of provincial power grids. Among them, the direct withdrawal of thermal power units from distributed new energy consumption operation will lead to a decrease in the stability of the power grid. When thermal power units are in peak shaving state, the impact on the transient stability of the power grid is relatively small.